Identifikasi komponen lipofilik fraksi n-heksan spons Agelas nakamurai asal Pulau Randayan Kalimantan Barat (Identification of lipophilic component of n-hexane fraction on Agelas nakamurai Sponge from Randayan Island, West Kalimantan) - Ajuk Sapar; Hamzi Anwari; Gusrizal Gusrizal (Marina Chimica Acta, 2013)
The isolation of lipophilic component of CC_7 on n-hexane fraction of Agelas nakamurai sponge has been conducted. The isolates are liquid oil colorless in 5.1 mg from 53,7 g sample. The isolates were analyzed by GC-MS and FTIR. The results of the analysis isolate CC_7 by FTIR showed the typical vibration of stretching at 2956,87 (asym. –CH3), 2924,09 (asym. –CH2), 2854,65 (sym. -CH3), 1730,15 (C=O), 1662,64 (C=C), 1595,13 (C-C(O)), 1269,16 (C-O), 1186,22 (C-C(O)-O), 1111,00 (O-C-C), 1020,34 (C-O-C-C), 962,48 (=C-H), 678,94 and 657,73 (cis –HC=CH–), bending rocking (-CH2-) at 731,02, bending (-CH2) dan (-CH3) at 1460,11 dan 1373,32. The results of GC-MS analysis showed the lipophilic component such as methyl palmitate (tR 19,77; m/z = 270), ethyl palmitate (tR 21,07; m/z = 284), palmitic acid (tR 21,18; m/z = 256, ethyl oleate (tR 24,09; m/z 310), tributyl asonitate (tR 24,38; m/z = 342), tributyl citrate (tR 24,95), tributyl acetyl (tR 26,41; m/z = 402), dioctyl adipate (tR 28,11; m/z =m 370, and squalene (tR 30,30; m/z 410).